HUBUNGAN STATUS GIZI TERHADAP TRIGLISERIDA DAN KOLESTEROL TOTAL PADA PASIEN DIABETES MELITUS (DM) TIPE 2 RAWAT JALAN DI RSPAD GATOT SOEBROTO PERIODE JUNI SAMPAI AGUSTUS 2013 - Shofia Nur Aini (2014)
Diabetes mellitus (DM) is a kind of metabolic disease characterized by hiperglicemia from the defect of insulin secretion, insulin action, or both. The major risk factor of DM is obesity, determined by Body Mass Index (BMI). High BMI as indicator of disfunction of lipid metabolism may increase dyslipidemia. DKI Jakarta as a capital city of Indonesia was declared being the second highest of DM patient in the nation. The purpose was to describe and found the relationship among nutrition status with triglycerides and total cholesterol of type 2 diabetes mellitus' (DM) patients in RSPAD Gatot Soebroto from June-August 2013. Total sample were 38 patiens. The obtained data were analyzed using the chi-square test. Prevalence of high BMI was 60,5%, unnormal triglyceride was 55,3%, unnormal total cholesterol was 63,2%. Based on analiyze from the chi square test for BMI and triglyceride obtained probability score (p)= 0,00, for BMI and total cholesterol obtained probability score (p)= 0,00. Scoring of P< α (0,05), there were a significant relationship among nutrition status with triglycerides and total cholesterol of type 2 diabetes mellitus' (DM) patients in RSPAD Gatot Soebroto from June-August 2013.